PENDUKUNG KEPUTUSAN PROMOSI JABATAN PADA PT. STARLIGHT GARMENT SEMARANG - Yuliana, Weni; Diartono, Dwi Agus (Proceeding SENDI_U, 2015)
System of promotion to employees at PT STARLIGHT GARMENT Semarang located in Semarang, precisely in this Bawen. Samban district system in PT. STARLIGHT GARMENT Semarang still using manual systems, andoften have many constraints faced by them required a long process and complicated, assessment calculation is invalid because it is not using the appropriate formula. Decision Support System Promoai Position ForEmployees be expanded by using sistemSDLC (system development life cycle), using the programming language PHP and MySQL database. The system is designed to enable managers to make decisions that employeesdeserve to be promoted, so that the whole process is done with a system that has been computerized, the method used in this research is the method of AHP that can take decisions effectively and with a validcalculation. Data collection method used is a field of study that includes interviews or direct FAQ systematically with the manager of PT. STARLIGHT GARMENT Semarang. literature study was also done by reading andstudying the books of literature relating to the decision support system.Keyword : Decision Support Systems, Promotions, AHP method, PHP and MySQL